ON INVESTIGATION OF TURKIC NUMERACY - Kulsaryieva, Aktolkyn; Zhumashova, Zhuldyz (European Scientific Journal, ESJ, 2014)
Turkic culture investigation is one of the less investigated cultures in Asia. One of the reason for this that being under the Soviet Union mainly Russian orientalist were concerned with research of Turkic cultures. This is not a secret that European and American Cultural Anthropologists and Ethnography scientists did not have permission and opportunity to investigate Central Asian Countries due to restrictions of Russian orientalists. However there have been made some investigations by French and German scholars. Beside this there can be found quantity of valuable information about Turkic culture in Chinese sources. In this article we will try to find out the peculiarities of Turkic numeracy based on multiple approaches including Western and American scholars’ investigation, Chinese and Russian scholars’ works and some Kazakh literature as one of the representatives of Turkic culture. In spite the wide-spread concept that numbers are universal and can be regarded as linguistic unit rather than to be an object of cultural anthropology, we are proving that Turkic numeracy has specific features which require special research. By numeracy can be covered wide range of concepts such as method of traditional chronology (twelve-year cycle system), number words etymology, numerical notation, age understanding in numbers, money and trading, counting and arithmetic and etc. Whole of this concepts are being investigated now. However in this article we have included only some key points regarding Turkic numeracy in general. So here you can get some information on main features of Turkic numeracy and its investigation issues.